2023
DOI: 10.1108/ijebr-01-2022-0085
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial business network and dynamic relational capabilities: a case study approach

Abstract: PurposeTo further extend the understanding of the aggregating functions of an entrepreneurial business network, this paper attempts to explore the antecedents enabling the organisation of diverse entrepreneurs to engage in a collaborative inter-firm business network project. This paper also elucidates the development of the relational capabilities and performance of entrepreneurial business networks.Design/methodology/approachAn explorative, longitudinal case study design is employed to analyse an Italian agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
(239 reference statements)
1
8
0
Order By: Relevance
“…The results of the study are supported by Yu and Zhou (2023) who found positive significant correlation between entrepreneurial networking resource(s) and SMEs performances. The study results are supported by Zardini et al (2023) who found positive significant correlation between networking structural dimensions and growth of enterprises. However, contradicted those of Maina et al (2020) who found that networking structural dimensions had no significant correlation with growth of enterprises in manufacturing SMEs in Kenya.…”
Section: Linear Regression Between Entrepreneurial Networking Practic...supporting
confidence: 73%
See 1 more Smart Citation
“…The results of the study are supported by Yu and Zhou (2023) who found positive significant correlation between entrepreneurial networking resource(s) and SMEs performances. The study results are supported by Zardini et al (2023) who found positive significant correlation between networking structural dimensions and growth of enterprises. However, contradicted those of Maina et al (2020) who found that networking structural dimensions had no significant correlation with growth of enterprises in manufacturing SMEs in Kenya.…”
Section: Linear Regression Between Entrepreneurial Networking Practic...supporting
confidence: 73%
“…Entrepreneurial network working practice is any upstream or downstream, formal or informal relationship that takes place between an enterprise and its local partners. This relationship is very critical for enterprise performance (Zardini et al, 2023). Additionally, entrepreneurial networks are social organizations offering different types of resources to start or improve entrepreneurial projects.…”
Section: Empirical Literaturementioning
confidence: 99%
“…At the organizational level, Zardini et al [12] explored the impact of corporate performance on entrepreneurial opportunistic behavior and discovered a negative correlation between firm performance and unethical conduct. The study attributed this finding to the strain theory, which posits that entrepreneurs are more likely to engage in unethical behavior when they experience pressure due to poor corporate performance and legitimate means are insufficient to achieve their objectives.…”
Section: Factors Influencing Ethical Decision Making and Behavior In ...mentioning
confidence: 99%
“…The undeniable importance of ethical behavior in entrepreneurship has long been recognized, yet extant research has revealed a disconcerting trend prevalent among entrepreneurs operating small businesses [11]. Typically, entrepreneurs exhibit a lack of attention to ethical challenges, which in turn engenders significant disparities in ethical attitudes and decision making between entrepreneurs and their non-entrepreneurial counterparts [12][13][14]. This reality can be largely attributed to the fact that entrepreneurs typically operate in high-stress business environments, wherein they struggle to find the necessary time and perspective for focused ethical reflection.…”
Section: Introductionmentioning
confidence: 99%
“…This study contributes to the current research on the role of entrepreneurs in sensing and seizing entrepreneurial opportunities through OI by examining the key roles of an entrepreneur and how a venture idea, once transformed into a business model, its development and launch with the help of a network of partners. Although research indicates that inter-firm engagement in a firm's network increases its innovation capabilities (Konsti-Laakso et al ., 2012; Zardini et al ., 2023), setting up and managing this network of partners is a new role for entrepreneurs once they start OI activities. This role is not well understood and is mismanaged in many innovation projects of SMEs, contributing to the high failure rate of open innovation projects initiated by SMEs.…”
Section: Introductionmentioning
confidence: 99%